2021
DOI: 10.1111/1750-3841.15626
|View full text |Cite
|
Sign up to set email alerts
|

Deodorization films based on polyphenol compound‐rich natural deodorants and polycaprolactone for removing volatile sulfur compounds from kimchi

Abstract: As natural polyphenols have been known to have the deodorizing activity, the deodorizing properties and mechanisms of action of polyphenols, the main constituents of green tea extract (GTE), black tea extract (BTE), and grape seed extract (GSE), against volatile sulfur compounds (VSCs) in kimchi were investigated. Six VSCs were targeted and detected to be in high abundance in kimchi. The deodorizing activity (%) toward VSCs was found to be in the following order: GSE (58.4 to 91.8) >GTE (37.6 to 73.8) >BTE (28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The analysis was performed according to the modified method of Jeong et al. (2021) in conformance with the ISO 17,299 standard. Standard solutions of the substances to be deodorized, acetic acid, and the four sulfur compounds (allyl methyl sulfide, dimethyl disulfide, allyl methyl disulfide, and diallyl disulfide) were prepared using methanol at a final concentration of 300 mM and 0.9 mL, and 0.1 g of the powder was used.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis was performed according to the modified method of Jeong et al. (2021) in conformance with the ISO 17,299 standard. Standard solutions of the substances to be deodorized, acetic acid, and the four sulfur compounds (allyl methyl sulfide, dimethyl disulfide, allyl methyl disulfide, and diallyl disulfide) were prepared using methanol at a final concentration of 300 mM and 0.9 mL, and 0.1 g of the powder was used.…”
Section: Methodsmentioning
confidence: 99%
“…These phenolic compounds can lyse the cell walls of microorganisms, disrupt membrane proteins, further damage various enzymatic systems, and inactivate genetic material in order to strengthen their antimicrobial properties [ 156 ]. Recent research has also indicated that phenolic compounds can be chemically reactive with various food constituents, such as proteins, or directly react with volatile odor compounds to modify the product’s flavor [ 157 , 158 ]. Furthermore, bacteriocins, namely, small bacterial peptides, showed strong antimicrobial activity.…”
Section: Odor Control Techniquesmentioning
confidence: 99%